2011
DOI: 10.1074/jbc.m111.240630
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Irradiation Can Induce Evasion of Colon Cancer Cells from Stimulation of Epidermal Growth Factor

Abstract: Receptor down-regulation is the most prominent regulatory system of EGF receptor (EGFR) signal attenuation and a critical target for therapy against colon cancer, which is highly dependent on the function of the EGFR. In this study, we investigated the effect of ultraviolet-C (UV-C) on down-regulation of EGFR in human colon cancer cells (SW480, HT29, and DLD-1). UV-C caused inhibition of cell survival and proliferation, concurrently inducing the decrease in cell surface EGFR and subsequently its degradation. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
(45 reference statements)
2
13
0
Order By: Relevance
“…Given the observed upregulation of p21WAF1 in our previous work [9], which is a cyclin dependent kinase inhibitor, we must assume that UV illumination causes the cells to arrest the cell cycle in G1 phase, which would be beneficial in inhibiting the proliferative potential of EGFR overexpressing cells. Adachi S. et al have also recently shown that UV irradiation can induce evasion of colon cancer cells from stimulation of epidermal growth factor [58]. They report that UV (254 nm) caused inhibition of cell survival and proliferation, concurrently inducing the decrease in cell surface EGFR and subsequently its degradation.…”
Section: Discussionmentioning
confidence: 96%
“…Given the observed upregulation of p21WAF1 in our previous work [9], which is a cyclin dependent kinase inhibitor, we must assume that UV illumination causes the cells to arrest the cell cycle in G1 phase, which would be beneficial in inhibiting the proliferative potential of EGFR overexpressing cells. Adachi S. et al have also recently shown that UV irradiation can induce evasion of colon cancer cells from stimulation of epidermal growth factor [58]. They report that UV (254 nm) caused inhibition of cell survival and proliferation, concurrently inducing the decrease in cell surface EGFR and subsequently its degradation.…”
Section: Discussionmentioning
confidence: 96%
“…Taking into consideration previous studies showing that EGF appears to regulate the survival time of Caenorhabditis elegans by activating proteasome [44] and that EGF increases proteasome expression through activation of EGFR in prostate cancer cells [45], our basic goal was to evaluate the effect of EGF/EGFR and then HER2 on the expression and the activity of the catalytic proteasome subunits. It is worth mentioning that in DLD-1 cancer cells, the introduction of exogenous EGF leads to phosphorylation of EGFR, as previously demonstrated [46]. As shown in Figure 1, EGF also significantly upregulated the expression of EGFR.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, we recently reported that UVC irradiation induces cell growth via downregulation of epidermal growth factor receptor (EGFR) (12) and also induces apoptosis (13) in human pancreatic cancer cells. Moreover, our recent study showed that UVC induced evasion of colon cancer cells from oncogenic stimulation by EGF (14). Hence, we believe that UVC could be applied for the clinical strategy against human malignancies including pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%